Elements In Gui Design For Islamic Tourism Mobile Applications: A Visual Research Framework - Ahmad Syukri Adnan; Mohammad Imran Ahmad; Noor Azli Mohamed Masrop; Naqibah Mansor; Mohammad Najib Jaffar (FSTM UIS, 2024)
Malaysian Journal of Information and Communication Technology (MyJICT) Volume 8 Issue 2 Page (146-155)